Well-concealed advanced duodenal carcinoma with Muir–Torre syndrome: a case report and review of literature - Tomoyuki Sugi; Osamu Shimomura; Shinji Hashimoto; Kazuhiro Takahashi; Manami Doi; Yoshihiro Miyazaki; Tsuyoshi Enomoto; Yoshimasa Akashi; Kazuhisa Araki; Tatsuya Oda (Surgical Case Reports)
Abstract Background Muir–Torre syndrome is an autosomal-dominant mutation in mismatch repair genes that gives rise to sebaceous tumors and visceral malignancies over time. Because colorectal and genitourinary cancers are common in Muir–Torre syndrome, duodenal carcinoma diagnoses are often delayed. Case presentation A 58-year-old woman presented with severe emaciation, anorexia, and upper abdominal pain. She had a history of rectal carcinoma, ascending colon carcinoma, and a right shoulder sebaceous carcinoma. Upper gastrointestinal endoscopy and computed tomography examinations suggested duodenal obstruction due to superior mesenteric artery syndrome, leading to long-term observation. Seven months later, she was finally diagnosed with duodenal carcinoma of the third portion. As the papilla of Vater was preservable due to tumor location, she received a partial duodenectomy in lieu of a pancreatoduodenectomy. Pathologically, the tumor was a well-differentiated adenocarcinoma with a classification of T3N0M0 Stage IIA (UICC, 8th edition). The postoperative course was uneventful and her appetite returned. A mutation in mismatch repair gene MSH2 confirmed the diagnosis of Muir–Torre syndrome genetically. Three years later, her nutritional status has fully recovered and she is free from both recurrence and metastasis. Conclusion In patients with comorbid skin sebaceous tumors and gastrointestinal malignancies, genetic screening is strongly recommended. Patients with Muir–Torre syndrome require long-term follow-up, and function-preserving treatment is desirable.